Distribution and habitat conditions of walleye pollock Theragra chalcogramma at southern Kuril Islands - S. L. Ovsyannikova; E. E. Ovsyannikov; Yu. V. Novikov (Известия ТИНРО)
Data on spatial distribution and habitat conditions are presented for walleye pollock Theragra chalcogramma at southern Kuril Islands in spawning season (spring 2015) and feeding season (summer 2016). In spring, walleye pollock are distributed over the entire shelf and continental slope down to 900 m depth and occupy the upper layer on the shelf and intermediate layer at the slope with water temperature 0.1–1.5 o C. In summer, they aggregate at the depth of 200–270 m beyond the shelf in the intermediate water at the Pacific slope of Iturup Island, under the temperature of 1.3–2.9 o C. Both spatial and bathymetric migrations of pollock are minimal at the Pacific side of Iturup, but they migrate for spawning westward and southwestward to the Okhotsk Sea and slope of Small Kuril Ridge where concentrate at the benthic front between the tidal mixing zone and the Intermediate water. Seasonal redistribution of walleye pollock is accompanied with changes of size-age structure in the main aggregations.